Assessment of Thyroid Profiles (TSH, T3 and T4) in HIV Positive Patients at Central Hospital, Benin City, Nigeria - , Omolumen, L.E.; , Iweka, F.K.; , Iyevhobu, K.O.; , Airhomwanbor, K.O.; , Usiobeigbe, O.S.; , Adelakun, A.A.; , Bisiriyu, A.H.; , Ikede, R.E.; , Ugege, C.; , Oboh, M.M.; , Asibor E.; , Adeji, A.J.; et al. (Archives of Current Research International, 2024)
This study evaluated the thyroid profile (TSH, T3 and T4) of HIV positive subjects visiting Central Hospital in Benin City, Edo State. The subjects in this study comprise of HIV positive volunteers aged between 18 to 50 years attending Central Hospital Benin City, Edo State, Nigeria. A total of 120 subjects were recruited for this study. The study comprises of eighty HIV positive subjects and forty apparently healthy subjects (controls). HIV serostatus was determined according to centre for disease and prevention. Plasma total TSH, T4 & T3 were quantitatively determined using enzyme immunoassay. TSH levels were significantly higher (p<0.05) in subjects (2.75±1.59 miu/ml) when compared with the control (1.92±1.11 miu/ml). T3 levels were not significantly lower (p>0.05) in subjects (1.32±0.63 ng/ml) when compared with the control (1.49±0.35 ng/ml). T4 levels were significantly lower (p<0.05) in subjects (6.06±1.83 µg/dl) when compared with the control (7.09±1.78 µg/dl). The results showed a significant non-increased in TSH (p>0.05) in subjects who had been on drugs within 11-15years, when compared with others. T3 and T4 levels were higher (p>0.05) in subjects who had been on drugs within 16-20 years when compared with other subjects. In conclusion, TSH levels were significantly higher (p<0.05) in subjects when compared with the control, and T4 levels were significantly lower (p<0.05) in subjects when compared with the control. Larger studies are needed to examine the epidemiology and health consequences of mild thyroid dysfunction in HIV-infected subjects and to better inform screening and treatment guidelines.